Experts Publish Sexual Dysfunction Guidelines. - Kaplan, Arline (Psychiatric Times, 2004)
The article focuses on the publication of various reports by 200 multidisciplinary experts from across 60 countries on the subject of sexual dysfunction in order to increase recognition and care. Recommendations for the creation of such papers emanated from the 2nd International Consultation on Sexual Medicine which was held in Paris, France from June 28 to July 1, 2003. Topics of the reports included orgasm disorders, epidemiology and risk factors of sexual dysfunction.